2014
DOI: 10.1186/1752-1947-8-341
|View full text |Cite
|
Sign up to set email alerts
|

Nasal high-flow oxygen therapy system for improving sleep-related hypoventilation in chronic obstructive pulmonary disease: a case report

Abstract: IntroductionSleep-related hypoventilation should be considered in patients with chronic obstructive pulmonary disease, because appropriate respiratory management during sleep is important for preventing elevation of PaCO2 levels. A nasal high-flow oxygen therapy system using a special nasal cannula can deliver suitably heated and humidified oxygen at up to 60 L/min. Since the oxygen concentration remains a constant independent of minute ventilation, this system is particularly useful in patients with chronic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…We earlier reported that HFNC use improved CO 2 narcosis in acute COPD exacerbations and improved sleep alveolar hypoventilation with PSG. 24 Bräunlich et al reported night-time use of an HFNC for 6 weeks in patients with stable hypercapnic COPD, but there was no significant difference from NPPV. Based on the present study, as well, it may be possible to prevent the onset of pulmonary hypertension and improve the prognosis of patients with chronic phase COPD by using HFNCs, which show high tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…We earlier reported that HFNC use improved CO 2 narcosis in acute COPD exacerbations and improved sleep alveolar hypoventilation with PSG. 24 Bräunlich et al reported night-time use of an HFNC for 6 weeks in patients with stable hypercapnic COPD, but there was no significant difference from NPPV. Based on the present study, as well, it may be possible to prevent the onset of pulmonary hypertension and improve the prognosis of patients with chronic phase COPD by using HFNCs, which show high tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in TcCO 2 correlates with the consistent rise in Vt, and we believe this increase may be accompanied by dead space and subsequent CO 2 washout, as seen in preceding COPD studies. 6 …”
Section: Discussionmentioning
confidence: 99%
“… 4 The observed clinical effects of high gas flows in patients with COPD include improvements in exercise tolerance, oxygenation and reduced dyspnoea. 5 6 NHF has been demonstrated to increase tidal volumes in a number of cohorts, 7 while reducing work of breathing by lowering inspiratory resistance and generating positive expiratory pressure. 5 NHF has been shown to be non-inferior to non-invasive ventilation in the prevention of treatment failure in patients with acute respiratory failure postcardiac surgery 8 and reduce mortality (both in the intensive care unit and at 90 days) in patients with acute respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…Two short studies and one case-report have described the effects of HFNC therapy on nocturnal hypoventilation. Okuda et al [ 73 ] reported a patient on HFNC therapy in whom the Apnea–Hypopnea Index decreased while oxygenation improved. HFNC therapy was continued at home without any recurrences of CO 2 narcosis.…”
Section: Clinical Applicationsmentioning
confidence: 99%